Answer:
(-3,-2)
Step-by-step explanation:
y = -x - 5
y = 2x + 4
plug in one of the y equations
(2x+4)= -x - 5
2x+4=-x-5
3x=-9
x= -3
plug in x to one of the y equations
y= -(-3) -5
y=3-5
y= -2
x= -3, y= -2
Answer:
8
Step-by-step explanation:
the pair of triangles is showing a dilations with a scale factor of 2
6/3=2
so it gives us 4 as the before answer and 4x2=8 so x=8
Answer: 1.03333333333
Step-by-step explanation:
3x - 2y = 8 +
===》 46x = 16
43x + 2y = 8
x = 16/46
x = 8/23
______________________________
3x - 2y = 8
3(8/23) - 2y = 8
24/23 - 2y = 8
2y = 24/23 - 8
y = 12/23 - 4
y = 12/23 - 92/23
y = - 80/23
Answer:
to me the answer will be 5 raised to power 2